Changes in population movement make COVID-19 spread differently from SARS - Shi, Q; Dorling, D; Cao, G; Liu, T (Elsevier, 2020)
This comment discusses the contribution of population movement to the spread of COVID-19, with a reference to the spread of SARS 17 years ago. We argue that the changing geography of migration, the diversification of jobs taken by migrants, the rapid growth of tourism and business trips, and the longer distance taken by people for family reunion are what make the spread of COVID-19 so differently from that of SARS. These changes in population movement are expected to continue. Hence, new strategies in disease prevention and control should be taken accordingly, which are also proposed in the comment.